2008
DOI: 10.1007/s00376-008-0709-x
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of East Asian climate to the progressive uplift and expansion of the Tibetan Plateau under the mid-Pliocene boundary conditions

Abstract: A global atmospheric general circulation model has been used to perform eleven idealized numerical experiments, i.e., TP00, TP10, · · · , TP100, corresponding to different percentages of the Tibetan Plateau altitude. The aim is to explore the sensitivity of East Asian climate to the uplift and expansion of the Tibetan Plateau under the reconstructed boundary conditions for the mid-Pliocene about 3 Ma ago. When the plateau is progressively uplifted, global annual surface temperature is gradually declined and st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
27
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 55 publications
3
27
0
1
Order By: Relevance
“…Kitoh (2004) also found that there are significant changes in the East Asian climate when the mountain reached about 60% of the present elevation. Jiang et al (2008) confirmed the 60% criteria by a different climate model. Modulations of El Niño/Southern Oscillation (ENSO) by mountain uplift are investigated by Kitoh (2007), where model ENSO becomes systematically weaker, shorter and less periodic when the mountain height increases.…”
supporting
confidence: 61%
“…Kitoh (2004) also found that there are significant changes in the East Asian climate when the mountain reached about 60% of the present elevation. Jiang et al (2008) confirmed the 60% criteria by a different climate model. Modulations of El Niño/Southern Oscillation (ENSO) by mountain uplift are investigated by Kitoh (2007), where model ENSO becomes systematically weaker, shorter and less periodic when the mountain height increases.…”
supporting
confidence: 61%
“…The elevation of the TP is assumed to increase linearly based on the present elevation, and this is referred to as plateau bulk uplift simulation. In such simulations, model results generally show that the uplift of the TP can induce, for instance, drier conditions in regions to the north and west of the TP, wetter conditions across the TP, and intensified Asian summer monsoon circulation and precipitation (Manabe and Terpstra, 1974;Ruddiman and Kutzbach, 1989;An et al, 2001;Liu and Yin, 2002;Jiang et al, 2008). However, this plateau bulk uplift simulation seems too simplistic when compared to the latest geological evidence of TP uplift, which suggests asynchronous uplifts across different regions of the TP (Tapponnier et al, 2001;Mulch and Chamberlain, 2006;Wang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The climatic effect of TP uplift is also of interest among paleoclimate researchers (Manabe and Terpstra, 1974;Kutzbach et al, 1989;Ruddiman and Kutzbach, 1989;Ramstein et al, 1997;An et al, 2001;Liu and Yin, 2002;Abe et al, 2003;Kitoh, 2004;Zhang et al, 2007a,b;Jiang et al, 2008;Lunt et al, 2010). These studies show that the uplift of the TP plays an important role in the formation and development of Asian monsoon climate and inland aridity.…”
Section: Introductionmentioning
confidence: 99%
“…The elevation of the principal part of TP is mainly over 4500 m. Therefore, the TP is also called the "Third Pole", and is sensitive to climate change. The thermal and dynamic processes over the TP also have great influence on the global climate change [15][16][17]. Many researches on the temperature variations over the TP have been done so far.…”
Section: Introductionmentioning
confidence: 99%